A 1T phase structure electrocatalyst and preparation method thereof
By growing the two -tadping platinum and the doped two -pyrophotic platinum of the 1T structure on the conductive background, it has formed an efficient electrocatalyst, solving the problem of insufficient activity of the base surface of the precious metal sulfide, significantly improved the catalytic activity and the catalytic activity and performance.
Patent Information
- Application Number
- CN202211645397.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-16
AI Technical Summary
As an electrocatalyst, noble metal sulfides have problems such as poor base surface activity and excessive interaction between layers, resulting in low catalytic performance.
The two -pyramid platinum and anionic doped binocroot are adopted by the 1T structure. Through the in -situ electrochemical deposition, high temperature ionization and the doping reactions of the anion, the electrical catalyst with better conductivity is formed.
The oxygen reduction catalysis of the electrocatalyst is improved, the hydrogen adsorption strength is enhanced, the problem of insufficient base surface activity of the precious metal sulfide is solved, and the efficient catalytic performance is achieved.
Smart Images

Figure CN115852430B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalysts, and in particular to an electrocatalyst with a 1T phase structure and a preparation method thereof. Background Art
[0002] With the development of industrial civilization, the use of fossil fuels has brought about significant scientific and technological progress in a short period of time. However, due to the sharp increase in the consumption of fossil fuels, it has also caused a serious burden on the environment. How to find green and renewable energy has become a topic of common concern to the world. Fuel cells can convert chemical energy into electrical energy. They are green, environmentally friendly, compact and have high energy density. They are one of the key technologies to cope with environmental crises and promote the transformation of energy technology. Electrocatalytic oxygen reduction (ORR) is one of the most important reactions in fuel cells. It plays a vital role in the adsorption of active oxygen and the desorption and conversion of hydrogen and oxygen products. In the ORR process, the electrocatalyst can significantly reduce the ORR activation energy and determine the conversion efficiency of chemical energy to electrical energy, that is, the utilization rate of the battery to the fuel. Therefore, the preparation of efficient and stable ORR electrocatalysts is the key to the commercialization of fuel cells.
[0003] Precious metal-based electrocatalysts such as Pt (platinum), Pd (palladium) and Au (gold) have become the mainstream electrocatalysts for commercial applications of fuel cells due to their excellent ORR performance. However, the rarity of precious metals has greatly limited the promotion of ORR technology in the new energy market. In recent years, some precious metal compounds have been used as ORR electrocatalysts, including: precious metal phosphides (such as PtP 2 , PdP 2 ), precious metal sulfides (such as PtSe 2 , PtTe 2 ) and noble metal borides (such as Pd 2 B), etc. Among them, two-dimensional metal sulfides have attracted extensive attention due to their unique physical and chemical properties such as large specific surface area, adjustable electronic structure, and high atomic utilization efficiency. Although noble metal sulfides have the advantage of two-dimensional structure, as metal sulfide materials, they have the "common problem" of poor basal activity and inability to provide sufficient active sites for the reaction. At the same time, the interlayer interaction of noble metal sulfides is extremely strong, and the electrical properties that are significantly dependent on the number of layers make it lack effective nano-scale means. Summary of the invention
[0004] The problem solved by the present invention is how to provide an effectively nanosized noble metal sulfide electrocatalyst, thereby improving the catalytic performance of the electrocatalyst.
[0005] To solve at least one aspect of the above problems, the present invention provides an electrocatalyst with a 1T phase structure, comprising a conductive substrate, and platinum ditelluride and anion-doped platinum ditelluride in-situ grown on the conductive substrate, wherein the platinum ditelluride and the anion-doped platinum ditelluride both have a 1T phase structure.
[0006] Preferably, the anions in the anion-doped platinum ditelluride include one or more of boron ions, carbon ions, nitrogen ions, fluorine ions, sulfur ions, sulfide ions and selenium ions.
[0007] Preferably, the ratio of the anion-doped platinum ditelluride is 5-15wt%.
[0008] Preferably, the platinum ditelluride and the anion-doped platinum ditelluride are both 1T phase two-dimensional structures.
[0009] Preferably, the conductive substrate comprises hydrophilic carbon cloth.
[0010] The present invention alleviates the problem of excessive expansion of the platinum ditelluride lattice by anion doping platinum ditelluride, optimizes the center position of the metal d orbital, shortens the distance between platinum atoms to improve the hydrogen adsorption strength, and effectively improves the oxygen reduction catalytic activity of the electrocatalyst, and platinum ditelluride and anion doped platinum ditelluride are both 1T phase structures, and have better conductivity. The 1T phase structure electrocatalyst provided by the present invention is an effectively nano-sized precious metal sulfide electrocatalyst, with strong catalytic activity and high catalytic performance, which solves the problems of poor basal activity of precious metal sulfides and low utilization of precious metals.
[0011] On the other hand, the present invention also provides a method for preparing an electrocatalyst with a 1T phase structure, which is used to prepare the electrocatalyst with a 1T phase structure as described above, comprising the following steps:
[0012] Step S1, in-situ electrochemically depositing a platinum nanosheet layer on a conductive substrate to obtain a conductive substrate loaded with platinum nanosheets;
[0013] Step S2, washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0014] Step S3, placing the pretreated conductive substrate in a tube furnace, performing high-temperature tellurization and anion doping reactions at 500-900° C. in an inert atmosphere, and obtaining an electrocatalyst with a 1T phase structure after cooling.
[0015] Preferably, in step S1, the conductive substrate is placed in an electrolyte containing chloroplatinic acid for in-situ electrochemical deposition, wherein the content of chloroplatinic acid in the electrolyte is 5-15 mM, and the pH of the electrolyte is 0.3-2.
[0016] Preferably, in step S1, a three-electrode system is used for in-situ electrochemical deposition, the potential during electrochemical deposition is set to -0.95 to -1.1 V, and the deposition time is set to 1000-3000 s.
[0017] Preferably, in step S3, the heating rate of the tube furnace is 3-20° C. / min, and the holding time is 2-8 h.
[0018] Preferably, in step S3, the inert atmosphere is an argon atmosphere, and the flow rate of the argon is 20-200 mL / min.
[0019] The present invention can obtain uniform platinum nanosheets on a conductive substrate through in-situ electrochemical deposition, and has a large specific surface area. The reaction is carried out under an inert atmosphere to avoid protecting the electrocatalyst from oxidation and avoiding the generation of impurities such as tellurium oxide. The reaction is carried out under a temperature condition of 500-900° C., which can ensure the generation of platinum ditelluride and anion-doped platinum ditelluride to form a 1T phase structure, while making the obtained electrocatalyst have more pores, which can serve as active sites for electrocatalytic reactions, thereby improving the catalytic activity of the electrocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a flow chart of a method for preparing an electrocatalyst in an embodiment of the present invention;
[0021] Figure 2 is the SEM image of the electrocatalyst in Comparative Example 1;
[0022] Figure 3 TEM of the electrocatalyst in Comparative Example 1 Figure 1 ;
[0023] Figure 4 TEM of the electrocatalyst in Comparative Example 1 Figure 2 ;
[0024] Figure 5 TEM of the electrocatalyst in Example 1 of the present invention Figure 1 ;
[0025] Figure 6 TEM of the electrocatalyst in Example 1 of the present invention Figure 2 ;
[0026] Figure 7 XRD patterns of different electrocatalysts;
[0027] Figure 8 A comparison chart of the ORR performance of different electrocatalysts. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0029] It should be noted that, in the absence of conflict, the features in the embodiments of the present invention can be combined with each other. The meanings of the terms "comprising", "including", "containing", and "having" are non-restrictive, that is, other steps and other ingredients that do not affect the results can be added. The above terms cover the terms "consisting of" and "essentially consisting of". Unless otherwise specified, materials, equipment, and reagents are commercially available.
[0030] The present invention provides an electrocatalyst with a 1T phase structure, comprising a conductive substrate and platinum ditelluride (PtTe) in situ grown on the conductive substrate. 2 ) and anion-doped platinum ditelluride, both the platinum ditelluride and the anion-doped platinum ditelluride have a 1T phase structure.
[0031] In order to reduce the cost of using precious metals and promote the development of water electrolysis technology, the construction of nanostructures, substrate regulation engineering, and transition metal alloys are commonly used catalyst optimization strategies to further improve the catalytic activity of electrocatalysts while reducing the amount of precious metals used. Precious metal compounds have a fixed crystal structure, which is convenient for identifying the real active sites and exploring new catalytic mechanisms. The formation of compounds can improve the coordination environment of precious metals, and can optimize the electronic structure and surface adsorption of precious metals through effects such as surface electrons, lattice strain, and orbital hybridization. In addition, the difference in electronegativity can cause a strong interaction between precious metals and anions, further awakening the inactivated metal active sites and improving the utilization rate of precious metals. Preparing precious metals into compounds and regulating their catalytic activity by anion doping can significantly improve the catalytic performance of precious metals.
[0032] Specifically, the embodiment of the present invention is to dope PtTe with anions. 2 Relieves PtTe 2 The problem of excessive lattice expansion is solved by optimizing the center position of the metal d orbital and reducing the distance between platinum atoms, thereby increasing the hydrogen adsorption strength and effectively improving the oxygen reduction catalytic activity of the electrocatalyst. 2 and anion-doped PtTe 2 They all have 1T phase structure and better conductivity.
[0033] In one embodiment, PtTe 2 and anion-doped PtTe 2 They are all 1T phase two-dimensional structures, that is, 1T phase layered structures. The 1T phase structure has higher conductivity, and the two-dimensional structure has a larger specific surface area, which can effectively expose the active sites of the electrocatalyst and improve the electrocatalytic activity.
[0034] In one embodiment, anion doped PtTe 2 The anions in the catalyst include one or more of boron (B) ions, carbon (C) ions, nitrogen (N) ions, fluorine (F) ions, phosphorus (P) ions, sulfur (S) ions and selenium (Se) ions. Boron ions are preferred. When boron ions are selected for doping, the redox effect of the electrocatalyst is better.
[0035] It should be noted that anion doping refers to the reaction of tellurium (Te) and platinum (Pt) to generate PtTe 2 When Te and other anions are doped in a certain proportion, they react with Pt.
[0036] Among them, anion doped PtTe 2 The ratio is 5-15wt%, that is, anion doped PtTe 2 PtTe 2 and anion-doped PtTe 2 The total mass ratio is 5-15%.
[0037] Doping PtTe with anions 2 The ratio of PtTe is set at 5-15wt%, which is not easy to generate impurities. 2 While maintaining the 1T phase structure, it is beneficial to reduce PtTe 2 The electron scattering at the center increases the carrier mobility.
[0038] It should be understood that when different anion doping is used, anion doping PtTe 2 The optimal ratio of will also change accordingly. For example, when boron ions are used for doping, anion doping of PtTe 2 The optimal ratio is 10%.
[0039] In one embodiment, the conductive substrate comprises hydrophilic carbon cloth.
[0040] Another embodiment of the present invention provides a method for preparing an electrocatalyst with a 1T phase structure, which is used to prepare the electrocatalyst with a 1T phase structure as described above. Figure 1 As shown, the following steps are included:
[0041] Step S1, in-situ electrochemically depositing a platinum nanosheet layer on a conductive substrate to obtain a conductive substrate loaded with platinum nanosheets;
[0042] Step S2, washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0043] Step S3, placing the pretreated conductive substrate in a tube furnace, performing high-temperature tellurization and anion doping reactions at 500-900° C. in an inert atmosphere, and obtaining an electrocatalyst after cooling.
[0044] Among them, in step S1, in order to avoid the influence of impurities, the conductive substrate is cleaned with acetone, ethanol and deionized water to obtain a conductive substrate with a clean surface, and then the conductive substrate with a clean surface is placed in an electrolyte for in-situ electrochemical deposition.
[0045] Wherein, the electrolyte contains chloroplatinic acid (H 2 PtCl 6 ) content is 5-15mM, and the pH of the electrolyte is 0.3-2. Select H with a pH of 0.3-2 and a concentration of 5-15mM 2 PtCl 6 As an electrolyte, it helps to form nanosheet morphology via in situ electrochemical deposition.
[0046] Specifically, chloroplatinic acid hexahydrate (H 2 PtCl 6 6H 2 O) was dissolved in deionized water to prepare a solution with a concentration of 5-15 mM, and then the pH of the solution was adjusted to 0.3-2 with hydrochloric acid to obtain a solution with a pH of 0.3-2 and a concentration of 5-15 mM. 2 PtCl 6 The solution is the electrolyte.
[0047] When performing in-situ electrochemical deposition, a three-electrode system is used for in-situ electrochemical deposition. The potential is set to -0.95V to -1.1V during electrochemical deposition, and the deposition time is set to 1000-3000s. In the three-electrode system, the working electrode is a conductive substrate, the counter electrode is a platinum sheet, and the reference electrode is Ag / AgCl. The potential is set to -0.95V to -1.1V to ensure that platinum can grow in situ on the conductive substrate, and the deposition time is set to 1000-3000s to ensure uniform growth.
[0048] In step S3, the pretreated conductive substrate and the tellurization and anion doping reaction raw materials are placed in the upstream and downstream of the heating zone of the tubular furnace, respectively, with a distance of 4-5.5 cm between them. The heating rate of the tubular furnace is set to 3-20°C / min, and the temperature in the tubular furnace is raised to 500-900°C, and kept at 500-900°C for 2-8 hours, wherein the inert atmosphere in the tubular furnace is an argon atmosphere, and the flow rate of argon is 20-200mL / min.
[0049] Among them, tellurium in the tellurization and anion doping reaction raw materials uses tellurium powder, which can avoid the introduction of oxygen impurities, and other anions use anion salts or corresponding single substances, such as sodium borohydride (NaBH 4 ), glucose, urea, ammonium fluoride (NH 4 F), phosphorus powder, sulfur powder and selenium powder. Preferably, the particle size of the tellurium powder is 5-10 μm.
[0050] The heating rate of the tubular furnace is set to 3-20℃ / min, which can ensure that the morphology of the platinum nanosheets will not be destroyed due to too fast heating during the heating process. After heating to 500-900℃ and keeping it warm for 2-8h, the tellurization and anion doping reactions can be complete. The tubular furnace is set to an argon atmosphere with an argon flow rate of 20-200mL / min, which can ensure that the platinum nanosheets on the pretreated conductive substrate can fully react with tellurium and other anions. If the argon flow rate is too slow, it is easy to fail to obtain effective inert gas protection. If the argon flow rate is too fast, it is easy to cause tellurium and other anions to fail to fully react with the platinum nanosheets, and it will cause argon waste.
[0051] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on the conditions recommended by the manufacturer.
[0052] Example 1
[0053] 1.1. Ultrasonic cleaning of the hydrophilic carbon cloth in acetone, ethanol and deionized water in sequence to obtain a cleaned hydrophilic carbon cloth;
[0054] 1.2. H 2 PtCl 6 6H 2 O was dissolved in deionized water to prepare a solution with a concentration of 8 mM, and then the pH of the solution was adjusted to 0.5 with hydrochloric acid to obtain an electrolyte;
[0055] 1.3. The cleaned hydrophilic carbon cloth was placed in an electrolyte and used as a working electrode in a three-electrode system. The platinum sheet was used as a counter electrode and Ag / AgCl was used as a reference electrode. In-situ electrochemical deposition was performed at a potential of -0.98 V for 1800 s. After the reaction was completed, a conductive substrate loaded with platinum nanosheets was obtained.
[0056] 1.4. Washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0057] 1.5. Mix Te powder and NaBH 4A mixture was prepared according to a mass ratio of 7:1, and the mixture was placed upstream of the heating zone of the tube furnace, and the pretreated conductive substrate was placed downstream of the heating zone of the tube furnace, with a spacing of 5.5 cm between them. After the tube furnace was purged, argon gas with a flow rate of 100 mL / min was introduced;
[0058] 1.6. The temperature of the tube furnace was raised to 740°C at a heating rate of 5°C / min, and then kept at this temperature for 5 hours. After the temperature in the tube furnace was naturally cooled to room temperature, an electrocatalyst was obtained, including a hydrophilic carbon cloth and PtTe in situ grown on the hydrophilic carbon cloth. 2 and boron-doped PtTe 2 .
[0059] Example 2
[0060] 2.1. Ultrasonic cleaning of the hydrophilic carbon cloth in acetone, ethanol and deionized water in sequence to obtain a cleaned hydrophilic carbon cloth;
[0061] 2.2. H 2 PtCl 6 6H 2 O was dissolved in deionized water to prepare a solution with a concentration of 9 mM, and then the pH of the solution was adjusted to 0.7 with hydrochloric acid to obtain an electrolyte;
[0062] 2.3. The cleaned hydrophilic carbon cloth was placed in an electrolyte and used as a working electrode in a three-electrode system. The platinum sheet was used as a counter electrode and Ag / AgCl was used as a reference electrode. In-situ electrochemical deposition was performed at a potential of -0.95 V for 1900 s. After the reaction was completed, a conductive substrate loaded with platinum nanosheets was obtained.
[0063] 2.4, washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0064] 2.5. Te powder and glucose were mixed in a mass ratio of 10:1, and the mixture was placed in the upstream of the heating zone of the tube furnace. The pretreated conductive substrate was placed in the downstream of the heating zone of the tube furnace, with a spacing of 4.5 cm between them. After the tube furnace was purged, argon gas with a flow rate of 40 mL / min was introduced;
[0065] 2.6. The temperature of the tube furnace was raised to 680°C at a heating rate of 3°C / min, and then kept at this temperature for 2 hours. After the temperature in the tube furnace was naturally cooled to room temperature, an electrocatalyst was obtained, including a hydrophilic carbon cloth and PtTe in situ grown on the hydrophilic carbon cloth. 2 and carbon ion-doped PtTe 2 .
[0066] Example 3
[0067] 3.1. Ultrasonic cleaning of the hydrophilic carbon cloth in acetone, ethanol and deionized water in sequence to obtain a cleaned hydrophilic carbon cloth;
[0068] 3.2. H 2 PtCl 6 6H 2 O was dissolved in deionized water to prepare a solution with a concentration of 12 mM, and then the pH of the solution was adjusted to 0.3 with hydrochloric acid to obtain an electrolyte;
[0069] 3.3. The cleaned hydrophilic carbon cloth was placed in an electrolyte and used as a working electrode in a three-electrode system. A platinum sheet was used as a counter electrode and Ag / AgCl was used as a reference electrode. In-situ electrochemical deposition was performed at a potential of -0.95 V for 1000 s. After the reaction was completed, a conductive substrate loaded with platinum nanosheets was obtained.
[0070] 3.4, washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0071] 3.5. Te powder and urea were mixed in a mass ratio of 10:1, and the mixture was placed in the upstream of the heating zone of the tube furnace. The pretreated conductive substrate was placed in the downstream of the heating zone of the tube furnace, with a spacing of 4 cm between them. After the tube furnace was purged, argon gas with a flow rate of 120 mL / min was introduced;
[0072] 3.6. The temperature of the tube furnace was raised to 790°C at a heating rate of 10°C / min, and then kept at this temperature for 8 hours. After the temperature in the tube furnace was naturally cooled to room temperature, an electrocatalyst was obtained, including a hydrophilic carbon cloth and PtTe in situ grown on the hydrophilic carbon cloth. 2 and nitrogen-doped PtTe 2 .
[0073] Example 4
[0074] 4.1. Ultrasonic cleaning of the hydrophilic carbon cloth in acetone, ethanol and deionized water in sequence to obtain a cleaned hydrophilic carbon cloth;
[0075] 4.2. H 2 PtCl 6 6H 2 O was dissolved in deionized water to prepare a solution with a concentration of 7 mM, and then the pH of the solution was adjusted to 0.8 with hydrochloric acid to obtain an electrolyte;
[0076] 4.3. The cleaned hydrophilic carbon cloth was placed in an electrolyte and used as a working electrode in a three-electrode system. The platinum sheet was used as a counter electrode and Ag / AgCl was used as a reference electrode. In-situ electrochemical deposition was performed at a potential of -0.95 V for 1100 s. After the reaction was completed, a conductive substrate loaded with platinum nanosheets was obtained.
[0077] 4.4. Washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0078] 4.5. Mix Te powder and NH 4 F is prepared into a mixture according to a mass ratio of 7:1, and the mixture is placed upstream of the heating zone of the tube furnace, and the pretreated conductive substrate is placed downstream of the heating zone of the tube furnace, with a spacing of 5 cm between them. After the tube furnace is purged, argon gas with a flow rate of 130 mL / min is introduced;
[0079] 4.6. The temperature of the tube furnace was raised to 630°C at a heating rate of 4°C / min, and then kept at this temperature for 7 hours. After the temperature in the tube furnace was naturally cooled to room temperature, an electrocatalyst was obtained, including a hydrophilic carbon cloth and PtTe in situ grown on the hydrophilic carbon cloth. 2 and fluoride-doped PtTe 2 .
[0080] Example 5
[0081] 5.1. Ultrasonic cleaning of the hydrophilic carbon cloth in acetone, ethanol and deionized water in sequence to obtain a cleaned hydrophilic carbon cloth;
[0082] 5.2. H 2 PtCl 6 6H 2 O was dissolved in deionized water to prepare a solution with a concentration of 13 mM, and then the pH of the solution was adjusted to 1.0 with hydrochloric acid to obtain an electrolyte;
[0083] 5.3. The cleaned hydrophilic carbon cloth was placed in an electrolyte and used as a working electrode in a three-electrode system. The platinum sheet was used as a counter electrode and Ag / AgCl was used as a reference electrode. In-situ electrochemical deposition was performed at a potential of -0.99 V for 2200 s. After the reaction was completed, a conductive substrate loaded with platinum nanosheets was obtained.
[0084] 5.4. Washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0085] 5.5. Te powder and P powder were mixed in a mass ratio of 15:1, and the mixture was placed in the upstream of the heating zone of the tube furnace. The pretreated conductive substrate was placed in the downstream of the heating zone of the tube furnace, with a spacing of 5.2 cm between them. After the tube furnace was purged, argon gas with a flow rate of 90 mL / min was introduced;
[0086] 5.6. The temperature of the tube furnace was raised to 840°C at a heating rate of 8°C / min, and then kept at this temperature for 4 hours. After the temperature in the tube furnace was naturally cooled to room temperature, an electrocatalyst was obtained, including a hydrophilic carbon cloth and PtTe in situ grown on the hydrophilic carbon cloth. 2 and phosphorus-doped PtTe 2 .
[0087] Example 6
[0088] 6.1. Ultrasonic cleaning of the hydrophilic carbon cloth in acetone, ethanol and deionized water in sequence to obtain a cleaned hydrophilic carbon cloth;
[0089] 6.2. H 2 PtCl 6 6H 2 O was dissolved in deionized water to prepare a solution with a concentration of 6 mM, and then the pH of the solution was adjusted to 0.5 with hydrochloric acid to obtain an electrolyte;
[0090] 6.3. The cleaned hydrophilic carbon cloth was placed in an electrolyte and used as a working electrode in a three-electrode system. The platinum sheet was used as a counter electrode and Ag / AgCl was used as a reference electrode. In-situ electrochemical deposition was performed at a potential of -0.95 V for 1700 s. After the reaction was completed, a conductive substrate loaded with platinum nanosheets was obtained.
[0091] 6.4. Washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0092] 6.5. Te powder and S powder are mixed in a mass ratio of 15:1, and the mixture is placed in the upstream of the heating zone of the tube furnace. The pretreated conductive substrate is placed in the downstream of the heating zone of the tube furnace, with a spacing of 4.5 cm between them. After the tube furnace is purged, argon gas with a flow rate of 90 mL / min is introduced;
[0093] 6.6. The temperature of the tube furnace was raised to 750°C at a heating rate of 7°C / min, and then kept at this temperature for 6 hours. After the temperature in the tube furnace was naturally cooled to room temperature, an electrocatalyst was obtained, including a hydrophilic carbon cloth and PtTe in situ grown on the hydrophilic carbon cloth. 2 and sulfur-doped PtTe 2 .
[0094] Example 7
[0095] 7.1. Ultrasonic cleaning of the hydrophilic carbon cloth in acetone, ethanol and deionized water in sequence to obtain a cleaned hydrophilic carbon cloth;
[0096] 7.2. H 2 PtCl 6 6H 2 O was dissolved in deionized water to prepare a solution with a concentration of 10 mM, and then the pH of the solution was adjusted to 0.4 with hydrochloric acid to obtain an electrolyte;
[0097] 7.3. The cleaned hydrophilic carbon cloth was placed in an electrolyte and used as a working electrode in a three-electrode system. The platinum sheet was used as a counter electrode and Ag / AgCl was used as a reference electrode. In-situ electrochemical deposition was performed at a potential of -0.95 V for 1800 s. After the reaction was completed, a conductive substrate loaded with platinum nanosheets was obtained.
[0098] 7.4. Washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0099] 7.5. Prepare a mixture of Te powder and Se powder in a mass ratio of 5:1, place the mixture upstream of the heating zone of the tube furnace, and place the pretreated conductive substrate downstream of the heating zone of the tube furnace, with a spacing of 5 cm between them. After purging the tube furnace, introduce argon gas at a flow rate of 180 mL / min;
[0100] 7.6. The temperature of the tube furnace was raised to 880°C at a heating rate of 5°C / min, and then kept at this temperature for 5 hours. After the temperature in the tube furnace was naturally cooled to room temperature, an electrocatalyst was obtained, including a hydrophilic carbon cloth and PtTe in situ grown on the hydrophilic carbon cloth. 2 and Selenium-doped PtTe 2 .
[0101] Comparative Example 1
[0102] 8.1. Ultrasonic cleaning of the hydrophilic carbon cloth in acetone, ethanol and deionized water in sequence to obtain a cleaned hydrophilic carbon cloth;
[0103] 8.2. H 2 PtCl 6 6H 2 O was dissolved in deionized water to prepare a solution with a concentration of 5 mM, and then the pH of the solution was adjusted to 0.3 with hydrochloric acid to obtain an electrolyte;
[0104] 8.3. Place the cleaned hydrophilic carbon cloth into an electrolyte and use it as a working electrode in a three-electrode system, use a platinum sheet as a counter electrode, and use Ag / AgCl as a reference electrode to perform in-situ electrochemical deposition at a potential of -0.95 V for 1500 s. After the reaction is completed, a conductive substrate loaded with platinum nanosheets is obtained;
[0105] 8.4. Washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate;
[0106] 8.5. Place Te powder upstream of the heating zone of the tube furnace, and place the pretreated conductive substrate downstream of the heating zone of the tube furnace, 5 cm apart from each other, and purge the tube furnace and introduce argon gas at a flow rate of 80 mL / min;
[0107] 8.6. The temperature of the tube furnace was raised to 700°C at a heating rate of 5°C / min, and then kept at this temperature for 5 hours. After the temperature in the tube furnace was naturally cooled to room temperature, an electrocatalyst was obtained, including a hydrophilic carbon cloth and PtTe in situ grown on the hydrophilic carbon cloth. 2 .
[0108] Experimental Example 1
[0109] The electrocatalyst in comparative example 1 was observed using a scanning electron microscope (SEM) and a transmission electron microscope (TEM) to obtain SEM images and TEM images, respectively, and the electrocatalyst in example 1 was observed using TEM to obtain a TEM image.
[0110] Among them, the SEM image of the electrocatalyst in Comparative Example 1 is as follows Figure 2 As shown in the TEM image Figure 3 and 4 As shown, the TEM image of the electrocatalyst in Example 1 is as follows Figure 5 and 6 shown.
[0111] from Figure 2 and Figure 3 It can be seen that the electrocatalyst is in the form of nanosheets and grows vertically on the surface of the hydrophilic carbon cloth, has a large specific surface area, and has a size of 100 nm. Since the preparation methods used in Comparative Example 1 and Example 1 are the same, only the raw materials are different, the above results show that the preparation method used in the embodiment of the present invention can obtain a nanosheet structure, increase the specific surface area of the electrocatalyst, and thus improve the catalytic activity and efficiency.
[0112] from Figure 4 It can be seen that the PtTe electrocatalyst in Comparative Example 1 2 It is a 1T phase structure with a lattice spacing of 0.3nm.
[0113] from Figure 5It can be seen that the electrocatalyst in Example 1 also has a nanosheet morphology and a size of 100 nm, which indicates that anion doping does not change the morphology and size of the electrocatalyst.
[0114] from Figure 6 It can be seen that the PtTe electrocatalyst in Example 1 2 and anion-doped PtTe 2 The same 1T phase structure, lattice spacing of 0.28nm. This shows that anion doping can make PtTe 2 The lattice shrinks, which is beneficial for regulating the electronic structure.
[0115] Experimental Example 2
[0116] X-ray diffraction tests were performed on the electrocatalysts in Examples 1-7 and Comparative Example 1 to obtain X-ray diffraction (XRD) patterns of the electrocatalysts. The results are as follows: Figure 7 shown.
[0117] from Figure 7 It can be seen that the PtTe in Comparative Example 1 2 And the anion-doped PtTe in Examples 1-7 2 The crystal structures of all samples were in 1T phase, and compared with the standard card PDF#00-018-0977, no segregation occurred.
[0118] Experimental Example 3
[0119] The ORR performance of the electrocatalysts in Example 1 and Comparative Example 1 were tested respectively. The results are as follows: Figure 8 shown.
[0120] Figure 8 is the oxygen reduction (ORR) analysis diagram, where PtTe 2 represents an electrocatalyst without anion doping, corresponding to the electrocatalyst in Comparative Example 1, B doped PtTe 2 Indicates B ion doped PtTe 2 , corresponding to the electrocatalyst in Example 1.
[0121] from Figure 8 It can be seen that B-doped PtTe 2 The limiting current density is 3 mA / cm 2 , the half-wave potential is 0.77 V, the initial potential is 0.84 V, and PtTe 2 The limiting current is 2.6 mA / cm 2 , the half-wave potential is 0.76 V, and the initial potential is 0.82 V. Boron ion doping makes PtTe 2 The current density, half-wave potential and initial potential are all improved, thereby enhancing the oxygen reduction performance of the electrocatalyst.
[0122] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. An electrocatalyst having a 1T phase structure, characterized in that: It comprises a conductive substrate, and platinum ditelluride and anion-doped platinum ditelluride in-situ grown on the conductive substrate. The platinum ditelluride and the anion-doped platinum ditelluride both have a 1T phase structure. The anions in the anion-doped platinum ditelluride include boron ions, and the proportion of the anion-doped platinum ditelluride is 5-15wt%.
2. The electrocatalyst of 1T phase structure according to claim 1, characterized in that: The conductive substrate includes hydrophilic carbon cloth.
3. A method for preparing an electrocatalyst with a 1T phase structure, for preparing an electrocatalyst with a 1T phase structure as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: Step S1, in-situ electrochemically depositing a platinum nanosheet layer on a conductive substrate to obtain a conductive substrate loaded with platinum nanosheets; Step S2, washing and drying the conductive substrate loaded with platinum nanosheets to obtain a pretreated conductive substrate; Step S3, placing the pretreated conductive substrate in a tube furnace, performing high-temperature tellurization and anion doping reactions at 500-900° C. in an inert atmosphere, and obtaining an electrocatalyst with a 1T phase structure after cooling.
4. The method for preparing the electrocatalyst with 1T phase structure according to claim 3, characterized in that: In the step S1, the conductive substrate is placed in an electrolyte containing chloroplatinic acid for in-situ electrochemical deposition, wherein the content of chloroplatinic acid in the electrolyte is 5-15 mM, and the pH of the electrolyte is 0.3-2.
5. The method for preparing the electrocatalyst with 1T phase structure according to claim 3, characterized in that: In the step S1, a three-electrode system is used for in-situ electrochemical deposition, the potential during electrochemical deposition is set to -0.95 to -1.1 V, and the deposition time is set to 1000-3000 s.
6. The method for preparing the electrocatalyst with 1T phase structure according to claim 3, characterized in that: In step S3, the heating rate of the tubular furnace is 3-20° C. / min, and the holding time is 2-8 h.
7. The method for preparing the electrocatalyst with 1T phase structure according to claim 3, characterized in that: In step S3, the inert atmosphere is an argon atmosphere, and the flow rate of the argon is 20-200 mL / min.
Citation Information
Patent Citations
Load-type monoatomic catalyst and preparation method thereof
CN109225257A
Preparation method of precious metal compound and application thereof
CN109904059A